2019
DOI: 10.1002/ajmg.b.32729
|View full text |Cite
|
Sign up to set email alerts
|

Study of C677T variant of methylene tetrahydrofolate reductase gene in autistic spectrum disorder Egyptian children

Abstract: Background: Autism spectrum disorders (ASD) is a heterogeneous neurodevelopmental disease, various articles reported that dysfunctional folate-methionine pathway enzymes might assume a paramount part in the pathophysiology of autism. Methylene tetrahydrofolate reductase (MTHFR) is a basic catalyst for this pathway, also MTHFR gene C677T variant accounted as a risk factor of autism.Objective: The present study aimed to investigate the association of MTHFR gene rs1801133(C677T) variant among Egyptian autistic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The folic acid metabolic-rate-limiting enzyme, methylenetetrahydrofolate reductase (MTHFR), also may play an important regulatory role in neurodevelopmental disorders such as autism (19,20). At the same time, there were also many reports that perinatal environmental factors such as low birth body mass may increase the risk of autism (10)(11)(12)(13)(14)(15)(16). The results of the present study also further confirmed some above-mentioned findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The folic acid metabolic-rate-limiting enzyme, methylenetetrahydrofolate reductase (MTHFR), also may play an important regulatory role in neurodevelopmental disorders such as autism (19,20). At the same time, there were also many reports that perinatal environmental factors such as low birth body mass may increase the risk of autism (10)(11)(12)(13)(14)(15)(16). The results of the present study also further confirmed some above-mentioned findings.…”
Section: Discussionsupporting
confidence: 90%
“…In a large-scale cross-country cohort study of more than two million people carried out by Ban et al (9), 22,156 of them were diagnosed with autism, with heritability of ∼80% but without support for maternal effect and environmental impact, indicating that the changes in the occurrence rate of autism in this population were mainly attributed to genetic impact. However, new evidence show that environmental factors also increase the risk of autism, such as prenatal estrogen, maternal body mass index (BMI), perinatal complications, birth season, birth body mass, and other environmental risk factors, as well as the interaction between heredity and environment, which are also related to the risk of autism (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an important consideration clarified the role of the MTHFR C677T polymorphism and ASDs (Table 3) [53,55,56,59]. A population-based case-control study in Chinese Han assessed the frequency of genotype MTHFR 677TT in 372 children.…”
Section: Studies On Mthfr Polymorphisms and Asdsmentioning
confidence: 99%
“…Also, a number of studies identified that several singlenucleotide polymorphisms (SNP) in different genes had relationship with ASD children. For example, SNPs in tryp-tophan hydroxylase 2 (TPH2), oxytocin receptor (OXTR), neuroligin1 (NLGN1) and methylenetetrahydrofolate reductase (MTHFR) were all found to have an association with ASD in diverse studies (10)(11)(12)(13). In the past three decades, HLA gene complex received increasing attention.…”
Section: Introductionmentioning
confidence: 99%